2012
DOI: 10.1021/nn300130q
|View full text |Cite
|
Sign up to set email alerts
|

Rough Fibrils Provide a Toughening Mechanism in Biological Fibers

Abstract: Spider silk is a fascinating\ud natural composite material. Its combination\ud of strength and toughness is unrivalled in\ud nature, and as a result, it has gained considerable\ud interest from the medical, physics,\ud and materials communities. Most of this\ud attention has focused on the one to tens of\ud nanometer scale: predominantly the primary\ud (peptide sequences) and secondary (β sheets,\ud helices, and amorphous domains) structure, with some insights into tertiary structure (the\ud arrangement of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
61
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 53 publications
4
61
0
Order By: Relevance
“…Such behaviour was only achieved provided that the fibrils were confined to dimensions below a critical length scale on the order of approximately 20-80 nm [37]. Experimental results indicate silk fibrils on the order of 20-200 nm in diameter [18,[38][39][40][41], suggesting a length scale in accordance with the benefits of such nanoconfinement. Moreover, another study [42]-motivated by continuum fracture mechanics criteria-indicated that silk toughness does not depend directly on nanostructure, but rather cohesive energy density (in collusion with a modulus contribution), and the fracture mechanics characteristics depends on micrometrescale dimensional features and attributable to its fineness.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Such behaviour was only achieved provided that the fibrils were confined to dimensions below a critical length scale on the order of approximately 20-80 nm [37]. Experimental results indicate silk fibrils on the order of 20-200 nm in diameter [18,[38][39][40][41], suggesting a length scale in accordance with the benefits of such nanoconfinement. Moreover, another study [42]-motivated by continuum fracture mechanics criteria-indicated that silk toughness does not depend directly on nanostructure, but rather cohesive energy density (in collusion with a modulus contribution), and the fracture mechanics characteristics depends on micrometrescale dimensional features and attributable to its fineness.…”
Section: Introductionmentioning
confidence: 99%
“…That being said, few studies have explicitly considered the contribution of interfibril interactions to the response of a thread. Recent atomic force microscopy (AFM) imaging has indicated that these fibrils are not homogeneous along the axis-they are characterized by globular protrusions at regular intervals ( figure 2a,b), increasing the fibril diameter over 50 per cent [41]. It has been proposed that these globules effectively form shear keys [41].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations